PENGARUH KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN HUTANG DAN DAMPAKNYA PADA ECONOMIC VALUE ADDED - Muchlasin, Mochamad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out the influence of managerial ownership to the debt policy and its impact to the economic value added (EVA). Samples in this research are manufacturing companies which are listed inthe Indonesia Stock Exchange (IDX) in the period of 2009-2011 by using purposive sampling method.Path analysis is the statistic method which is used in this research.Â  Variables in this research are Managerialownership (INSDR) as the independent variables, debt policy as the intervening variable and Economic ValueAdded as the dependent variable.The result of research shows that INSDR has insignificant positive influence to the EVA, this result is related toArry Irawan research (2009) and Yuni Puspita Sari research (2013). INSDR has significant negative influenceto DER, this result is related to Siswandi research (2011) and Lenra Juni Remember Purba research (2011),while DER has significant negative influence to the EVA, this result is related to Yuni Puspita Sari research(2013). DER is proven to be the intervening variable which mediates the influence of INSDR with EVA. Keywords: Managerial Ownership, Debt Policy, Economic Value Added, Manufacturing Companies